Analyzing Social Capital Behaviour in the Renewable Energy Sector of Nepal (United Journal of Interdisciplinary Studies, 2024)
This paper aims to analyze social capital behaviour in the context of the renewable energy sector in Nepal, comprising a descriptive cum analytical research design based on both primary and secondary data. Some necessary primary data were collected by conducting a field survey using a structured questionnaire on a sample of 118 Nepalese renewable energy enterprises having 264 respondents. Likewise, its secondary data were collected through relevant publications. The collected data were analyzed using simple statistical tools through SPSS to derive results leading to major findings of the study. The study concluded that renewable energy entrepreneurs feel closeness with family networks/members and social networks, but they have frequent contact with an internal network of employees as well as buyer-supplier networks. Furthermore, trust among networks provides an opportunity to create a high level of trust among the members while the shared vision provides an opportunity for personal socializing among entrepreneurs so that members expend resources in terms of time, money, equipment, or excess inventory for helping each other leading to achieving the goals of the enterprises. Policy implications and future avenues are also discussed for sustainable energy sector of Nepal.